Analysis of the Relationship Between Waiting Time for Compounded and Non-Compounded Prescription Services and BPJS Patient Satisfaction Levels at Community Health Centers (Puskesmas) - Kurniasih, Nia; Harun, Nurhidayati; Ramdhani , Susan Sintia; Indriastuti, Marlina; Romansyah, Anton Andhi (INDOGENIUS, 2025)
Background & Objective :  This study aims to analyze the relationship between the waiting time for compounded and non-compounded prescription services and the satisfaction level of BPJS patients at the Ciamis Community Health Center (Puskesmas). Method: The study employed an analytical survey method with a cross-sectional design. A total of 98 outpatients who met the inclusion criteria were sampled. The instruments used included a satisfaction questionnaire and a stopwatch to record waiting times. Data were analyzed using the chi-square test with a significance level of <0.05. Result: The results showed that the waiting time for compounded prescriptions was 100% compliant with the standard, while for non-compounded prescriptions, it was 95.5% compliant. Patient satisfaction with compounded prescription services was 100%, and for non-compounded prescriptions, it was 98.9%. A significant relationship was found between prescription service waiting times and patient satisfaction levels, with a p-value of 0.041 (<0.05). Conclusion: This study concludes that there is a significant relationship between waiting time and patient satisfaction levels at the Ciamis Community Health Center.